The attachment sites and attachment areas of deltoid ligament related to clinical implications: A cadaveric study - Chanatporn Inthasan (2020)
© Universidad de la Frontera. All rights reserved. Currently, the treatment for patients with deltoid ligament injuries who require surgical treatment are anatomical repair and reconstruction. The clinicians should understand the exact knowledge of attachment areas of individual bands of deltoid ligament for a successful treatment. We studied 46 ankles of fresh frozen cadavers. The individual bands of deltoid ligament were divided to small fibers. Afterwards, each small fiber of each band was cut and marked with acrylic color on the origin and insertion followed by photo taking. Lastly, the photos of individual origin and insertion were used to calculate the attachment areas. We found six bands of deltoid ligament in all ankles except tibionavicular ligament. Moreover, we discovered deep to tibiocalcaneal and posterior to sustentaculum tali ligaments in 3 cases. Regarding the attachment area, the deep posterior tibiotalar ligament had the largest proximal and distal attachment areas which were 87.36±23.15 mm2 and 88.88±24.24 mm2, respectively. The anterior tibiotalar ligament had the least proximal and distal attachment areas which were 23.12±8.25 mm2 and 33.16±14.63 mm2, respectively. Hence, the accuracy and exact areas of attachment of deltoid ligament are important as it can help clinicians to select the suitable treatments including injury prevention.